The University as a catalyst in the processes of Adult Continuing Education (ACE) - Stefano Bonometti; Letizia Ferri (Firenze University Press, 2024)
The article analyzes the cooperation between university researchers and local stakeholders in promoting adult continuing education (ACE) through action research. It outlines four projects conducted at the Chair of Pedagogy at the University of Insubria, through which innovative solutions have been developed in various sectors using research and social learning methodologies. The RE-START project involved establishing community tables at the local level, the Adolescent Tables of the Municipality of Varese were structured according to the Change Laboratory logic, the Morselli Project implemented a Service Learning approach in collaboration with local schools, and vertical Communities of Practice were developed for the co-construction of school guidance modules with secondary schools. In all these projects, the University positioned itself as a catalyst and activator of the agency of the adults with whom it collaborated and co-designed.   Il ruolo dell'Università come catalizzatore nei processi di Educazione Continua per Adulti (ECA). L'articolo analizza la cooperazione tra ricercatori universitari e operatori territoriali nel promuovere l'educazione continua per adulti (ECA) attraverso la ricerca-azione. Si delineano quattro progetti condotti presso la cattedra di Pedagogia dell'Università degli Studi dell'Insubria, attraverso i quali sono state costruite soluzioni innovative in diversi settori tramite metodologie di ricerca e apprendimento sociale. Il progetto RE-START ha visto l'istituzione di tavoli di comunità a livello locale, i Tavoli Adolescenti del Comune di Varese sono stati articolati secondo la logica del Change Laboratory, il Progetto Morselli ha implementato un approccio di Service Learning in collaborazione con le istituzioni e le scuole locali, sono state sviluppate Comunità di Pratica verticali per la co-costruzione di moduli di orientamento scolastico con le scuole secondarie. In tutti questi progetti l'Università si è posta come lievito ed attivatore dell'agency degli adulti con cui ha collaborato e co-progettato.